Antibacterial activity of tannins towards Pseudomonas syringae pv. tomato, and their potential as biostimulants on tomato plants - CANZONIERE, Paolo; FRANCESCONI, Sara; GIOVANDO, Samuele; BALESTRA, Giorgio (Phytopathologia Mediterranea, 2021)
Pseudomonas syringae pv. tomato (Pst), the causal agent of bacterial speck of tomato, is a significant cause of economic losses in tomato crops. This disease is mainly controlled with preventive use of cupric salt formulations. Antibacterial activity of the tannins U1, U2, U3 and U4, applied alone at 1% w/v concentration or in combination with half (0.045% w/v) of standard of copper hydroxide treatments, was assayed for effects on Pst. In vitro, the four tannins completely inhibited Pst colony formation after 24 h, but U2 (quebracho tannins) + ½ Cu(OH)2 allowed Pst growth after 48 h of incubation, indicating that, since U2 is composed of high molecular condensed tannins it is likely that their structures have chelated the copper hydroxide much more then hydrolysable ones, thus inactivating copper hydroxide and tannins. In fact, this activity of the tannins was equivalent to that for 0.045% w/v of copper hydroxide. Effects of tannins on tomato plant growth were also assessed. On seedlings, long-term U1 treatments increased dry weight of shoots compared to copper hydroxide, but not to water treatment. The U4 treatment increased the NBI values compared to copper treatment but did not show significant differences compared to the water treatment. Inhibitory activity of tannin treatments reduced disease by 37–62%, and 60% after copper treatment, while disease severity was reduced by 33–54% after treating plants with tannins and 36% after copper treatment. On mature plants treated once, the disease reduction was 27–39% after tannin treatments and 44% after copper treatment, while severity was reduced by 50–60% from tannin treatments, and 47% by copper. In seedlings and mature plants, these reductions were similar (P > 0.05) for the tannins and copper treatments. This study indicates a novel crop protection strategy using natural products as alternatives to xenobiotic compounds.